LAYANAN KONSELING ISLAMI BAGI KESULITAN BELAJAR DALAM PENDIDIKAN ISLAM - Suriyadi Suriyadi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Guidance and counseling is very instrumental in helping students achieve education. The students need to be guided, so that they can optimize its potential. Learning problems are important problems. This  was proved from a result of research at several schools in Yogyakarta, which indicated that the difficulties in learning to be a problem that is most prominent among the problems faced by students. The difficulties that was experienced by learners psychologically are academic delays, very slow in learning as a result of having inadequate intelligence, poor habit in learning and unhealthy emotional mental. The way to identify students’ learning disabilities are through behavior, and through the analysis of learning achievement.